Fast sulfur dioxide measurements correlated with cloud condensation nuclei spectra in the marine boundary layer - D. C. Thornton; A. R. Bandy; J. G. Hudson (Atmospheric Chemistry and Physics, 2011)
During the Rain in (shallow) Cumulus over the Ocean (RICO) project simultaneous high rate sulfur dioxide (SO2) measurements and cloud condensation nuclei (CCN) spectra were made for the first time. For research flight 14 (14 January 2005) the convective boundary layer was impacted by precipitation and ship plumes for much of the midday period but not in the late afternoon. Number densities of accumulation mode aerosols (0.14 to 0.2 μm diameter) were a factor of two greater in the later period while CCN were 35% to 80% greater for aerosols that activate at supersaturations >0.1%. Linear correlations of SO2 and CCN were found for SO2 concentrations ranging from 20 to 600 parts-per-trillion (pptv). The greatest sensitivities were for SO2 and CCN that activate at supersaturations >0.1% for both clean and polluted air. In a region unaffected by pollution SO2 was linearly correlated only with CCN at >0.2% supersaturation. These correlations imply that the smallest CCN may be activated by SO2 through heterogeneous conversion. Evidence for entrainment of CCN from the cloud layer into the CBL was found.